Model matematis salinitas air di muara sungai untuk pengairan tambak udang windu(Studi kasus di panatai utara kabupaten Karawang) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
The main cause of the failure of water pond is the fluctuation of water quality. This research aims at testing two models, which are able to describe the _fluctuation of water salinity as one of the water quality parameters. The research was conducted in Muara Sedari, Karawang from November to December 2002. The two models applied were Mixed-Salinity Model and Cosines Model. Mixed salinity model predicts salinity in river mouth through computation of salinity of both river and sea which are mixed in. Cosines model predicts salinity of water in river mouth as considering sea tidal and river discharge. Cosines Models consists of two models. namely Tidal Model and Salinity Regression Model. Output of Tidal Model becomes one of the inputs of Salinity Regression Model. In this research .four types of Salinity Regression Model were tested. Salinity of water from the study area was measured using Argentometry method and the observed data were used to validate the model. Results indicated that all models are applicable, however, Cosines Alodel using Second Degree Polynomial Model has the best agreement.